Actores educativos y su participación en el desarrollo curricular desde la aplicación de sistemas - Avendaño, Henry Alonso González (RISTI : Revista Ibérica de Sistemas e Tecnologias de Informação, 2023)
Palabras-clave: Actores Educativos, Participación, Recorrido histórico Abstract: This article develops a historical overview of some of the representative authors associated with the curriculum and presents a set of studies and reflections on the relationship between educational actors and curriculum design. The methodology used is the documentary review, which was distributed in the categories of "educational actors", "curriculum design" and "relationship between educational actors and curriculum design". [...]the curricular conceptions of authors such as Franklin Bobbit, Ralph Tyler, Hilda Taba, Philip W. Jackson, Joseph Schwab, Lawrence Stenhouse, John Eggleston, Stephen Kemmis, José Gimeno Sacristán and Abraham Magendzo are observed, with the aim of generating a reflection on the evolution of the role of educational actors in the exercise of curriculum construction, and then the main findings associated with the studies and reflective articles mentioned are presented. Su mayor aportación en la historia del currículo es lo que se conoce como el modelo de Tyler, que se basa en una enseñanza por objetivos y una educación conductista en la que no se tienen en cuenta los